Uterine Myxoid Leiomyosarcoma with Stromal Chondroid Metaplasia: A Rare Case Report: - Akbarzadeh-Jahromi, Mojgan; Sari Aslani, Fatemeh; Taheri, Negar; Najib, Fatemehsadat (Galen Medical Journal, 2021)
Background: Uterine leiomyosarcoma is a rare gynecological disease. Myxoid leiomyosarcoma (mLMS) is an aggressive and very uncommon type of leiomyosarcoma, with few cases reported in English literature. Stromal metaplasia is rare in leiomyosarcoma. Here we present huge uterine myxoid leiomyosarcoma with stromal chondroid metaplasia. Case Report: A 48–year–old single woman with lower abdominal pain and increased abdominal circumference. The detected mass on imaging was diagnosed as uterine mLMS with stromal chondroid metaplasia in the histopathological examination after surgery. Conclusion: Myxoid leiomyosarcoma should be considered in uterine mass with extensive myxoid change, infiltrative border, low mitotic count, and mild atypia. Stromal chondroid metaplasia can be seen in the myxoid leiomyosarcoma. [GMJ.2021;10:e1817]